Away from the numbers. (1st January 2014) - Donleavy, Gabriel D.
"The concoctions of the culture industry are neither guides for a blissful life, nor a new art of moral responsibility, but rather exhortations to toe the line, behind which stand the most powerful interests. The consensus which it propagates, strengthens blind, opaque authority" [Adorno, (2001), p.105]. This paper explores the extent to which some of the pop icons of the 60s and 70s falsify Adorno's view. It describes how pop stars related to left politics through music, and how pop heroes of the left have flared up and flipped out. It considers how mainstream icons of 60s and 70s rock music diluted the revolutionary energies of their time and how they filtered disillusion with the hopes and dreams that failed to materialise. Special focus is on the late 60s and on Mick Jagger, and the significance of his temporary 'SFTD' as an anthem of greater revolutionary potential than his fence sitting 'SFM'. Adorno's thesis is largely supported and the strongest of the possible counter–factuals in the two decades reviewed are given their due.